Safety and Tolerability of Burst-Cycling Deep Brain Stimulation for Freezing of Gait in Parkinson’s Disease - Wong, Joshua K.; Hu, Wei; Barmore, Ryan; Lopes, Janine; Moore, Kathryn; Legacy, Joseph; Tahafchi, Parisa; Jackson, Zachary; Judy, Jack W.; Raike, Robert S.; Wang, Anson; Tsuboi, Takashi; et al. (Frontiers in Human Neuroscience, 2021)
Background: Freezing of gait (FOG) is a common symptom in Parkinson’s disease (PD) and can be difficult to treat with dopaminergic medications or with deep brain stimulation (DBS). Novel stimulation paradigms have been proposed to address suboptimal responses to conventional DBS programming methods. Burst-cycling deep brain stimulation (BCDBS) delivers current in various frequencies of bursts (e.g. 4-Hz, 10-Hz or 15-Hz), while maintaining an intra-burst frequency identical to conventional DBS. Objective: To evaluate the safety and tolerability of BCDBS in PD patients with FOG. Methods: Ten PD subjects with STN or GPi DBS and complaints of FOG were recruited for this single center, single blinded within-subject crossover study. For each subject, we compared 4-Hz, 10-Hz and 15-Hz BCDBS to conventional DBS during the PD medication-OFF state. Results: There were no serious adverse events with BCDBS. It was feasible and straightforward to program BCDBS in the clinic setting. The benefit was comparable to conventional DBS in measures of FOG, functional mobility and in PD motor symptoms. BCDBS had lower battery consumption when compared to conventional DBS. Conclusions: BCDBS was feasible, safe and well tolerated and it has potential to be a viable future DBS programming strategy.